Guidance in Mass Media – Analysis of the Selected Examples - Dąbrowska-Cendrowska, Olga (Respectus Philologicus, 2018)
Guidance in media is not a new phenomenon. Looking for the answers to more or less complex questions about human existence seems to be as old as human society. A great deal of books are guidance books. Guidance has always been present in the press. Guidance programmes are also found on television. The Internet is dominated by the communication guidance based on one to one or/and one to few principles. However, the popularity of some websites, portals and blogs makes this way of communication similar to the traditional, periodical mass media (one-to-many).Contemporary media, and to be more precise, media offer has become a commodity. In order to be sold, it undergoes the processes of tabloidisation. Due to this, the owners can count on higher profits as the product reaches a larger audience. Guidance in press and on television has become one of the ways to make money.The article is based on the offer addressed to the female mass audience and is an attempt to answer the questions: what are the characteristics of mass guidance, what subject matter dominates in the popular media offer addressed to the mass audience, and what benefits does the sender get from the message?